Correlating Psychological Comorbidities and Outcomes After Spine Surgery. Issue 7 (October 2020) - Jackson, Keith L.; Rumley, Jacob; Griffith, Matthew; Agochukwu, Uzondu; DeVine, John
Study Design: Literature review. Objective: The aim of this literature review is to examine the effects of psychological disorders on postoperative complications, surgical outcomes, and long-term narcotic use. We also hope to detail the value of preoperative identification and treatment of these pathologies. Methods: A series of systematic reviews of the relevant literature examining the effects of psychological disorders and spine surgery was conducted using PubMed and Cochrane databases. Results: Combined, the database queries yielded 2275 articles for consideration. After applying screening criteria, 96 articles were selected for inclusion. Patients with underlying psychological disease have higher rates of delirium, readmission, longer hospital stays, and higher rates of nonroutine discharge following spine surgery. They also have higher rates of chronic postoperative narcotic use and may experience worse surgical outcomes. Because of these defined issues, researchers have developed multiple screening tools to help identify patients with psychological disorders preoperatively for potential treatment. Treatment of these disorders prior to surgery may significantly improve surgical outcomes. Conclusion: Patients with psychological disorders represent a unique population with respect to their higher rates of spinal pain complaints, postoperative complications, and worsened functional outcomes. However, proper identification and treatment of these conditions prior to surgery may significantly improve many outcome measures in this population. Future investigations in this field should attempt to develop and validate current strategies to identify and treat individuals with psychological disorders before surgery to further improve outcomes.